2012
DOI: 10.1038/nature11336
|View full text |Cite
|
Sign up to set email alerts
|

Revealing structure and assembly cues for Arabidopsis root-inhabiting bacterial microbiota

Abstract: The plant root defines the interface between a multicellular eukaryote and soil, one of the richest microbial ecosystems on Earth. Notably, soil bacteria are able to multiply inside roots as benign endophytes and modulate plant growth and development, with implications ranging from enhanced crop productivity to phytoremediation. Endophytic colonization represents an apparent paradox of plant innate immunity because plant cells can detect an array of microbe-associated molecular patterns (also known as MAMPs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

172
1,733
11
17

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,039 publications
(1,933 citation statements)
references
References 21 publications
172
1,733
11
17
Order By: Relevance
“…Previous studies have reported appreciable numbers of antibiotic resistant members on the consumer-ready vegetables, such as lettuce and spinach leaves [17,46,47]. Root endophytes can be recruited from common soil bacteria and survived in the interior of the root [48,49], which allow ARGs transferring from soil into plant. Microorganisms can also be colonized in leaf tissue as leaf endophytes [50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported appreciable numbers of antibiotic resistant members on the consumer-ready vegetables, such as lettuce and spinach leaves [17,46,47]. Root endophytes can be recruited from common soil bacteria and survived in the interior of the root [48,49], which allow ARGs transferring from soil into plant. Microorganisms can also be colonized in leaf tissue as leaf endophytes [50].…”
Section: Discussionmentioning
confidence: 99%
“…When combined with quantitative and high-resolution bacterial profiling methods such as pyrosequencing, some of these variations can be directly correlated to the level of silencing to better interpret the results. Previous studies used sonication to either separate rhizosphere soil from nonrhizosphere soil or to isolate one region of the rhizosphere (Bulgarelli et al 2012;Doi 2007). We used successive sonication to reproducibly isolate different soil fractions with specific bacterial composition.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have identified the influence of plant genotype and the environment on the composition and diversity of rhizosphere microbiota (Bulgarelli et al 2012;Gottel et al 2011;Peiffer et al 2013;Philippot et al 2013). In addition, either the roles of specific compounds in rhizodeposits, the roles of specific cellular transport machinery on rhizosphere microbial diversity, or both have been investigated (Bais et al 2006;Walker et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that many kinds of bacteria live in and around plant roots, including the phyla Proteobacteria, Actinobacteria (Gram-positive high G+C bacteria), Bacteroides and Verrucomicrobia, which have been detected by pyrosequencing. [3][4][5] Over 40 genera of filamentous Actinobacteria (actinomycetes) have been detected from Triticum aestivum roots alone by terminal restriction fragment length polymorphism. 6 Bacteria exist on the surface and inside of plant roots, as demonstrated by fluorescence in situ hybridization, scanning electron microscopy or detection of target genes.…”
Section: Introductionmentioning
confidence: 99%
“…6 Bacteria exist on the surface and inside of plant roots, as demonstrated by fluorescence in situ hybridization, scanning electron microscopy or detection of target genes. [7][8][9][10] Numerous bacteria live in rhizospheres, up to 10 6 cells per mm 3 , including filamentous bacteria with actinomycetes accounting for an estimated 4% of the total. 9 This shows the relationship that exists between actinomycetes and plants.…”
Section: Introductionmentioning
confidence: 99%